1999
DOI: 10.1007/bf01298961
|View full text |Cite
|
Sign up to set email alerts
|

Retrospektive Bewertung des Therapieerfolgs bei kieferorthop�discher Behandlung von Erwachsenen

Abstract: The aim of this study was the retrospective evaluation of the outcome of orthodontic treatment in consecutively treated adult patients. Of 147 adult patients, it was possible to evaluate the records of 88 patients (57 female, 31 male) before (T1) and after treatment (T2), and of 20 of these patients 3.3 years on average after completion of the retention phase (T3). During treatment planning, a nearly "ideal" result was considered attainable (ideal group) for 46 patients, and a "compromise" result (compromise g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…(16) and Hassan (21) encountered higher values – treatment needs of 48.8% and 71.6% respectively but their samples present an important selection bias in that they were made up of patients visiting orthodontics units for treatment. Equally, Riedmann and Berg (25) found a 60.2% treatment need, but their sample was composed of 88 orthodontic patients. Tang and So (13) and So and Tang (26), who respectively obtained 54.2% and 53% treatment needs, also display evident sample selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…(16) and Hassan (21) encountered higher values – treatment needs of 48.8% and 71.6% respectively but their samples present an important selection bias in that they were made up of patients visiting orthodontics units for treatment. Equally, Riedmann and Berg (25) found a 60.2% treatment need, but their sample was composed of 88 orthodontic patients. Tang and So (13) and So and Tang (26), who respectively obtained 54.2% and 53% treatment needs, also display evident sample selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] The paper of greatest relevance to the current audit is that by O'Brien et al in 1993, 5 in which the authors looked at 17 hospital departments and investigated some 1,392 cases treated with fixed appliances. They examined all cases, including those in which the appliances were removed early, and included all grades of operator.…”
Section: Setting a Standardmentioning
confidence: 99%
“…Different normal ranges of linear values for OJ and OB are defined [2228] depending on their impact on the different physiological aspects of the stomatognathic system (Table 1). Ioannidou et al [23], Lowe et al [29], and Riedman and Berg [30] described an interdependence between OJ and OB and craniofacial morphology. Kessler [31] and Silness and Roynstrand [32] showed that the OJ/OB relationship affects periodontal conditions.…”
Section: Introductionmentioning
confidence: 99%